1990
DOI: 10.1128/jvi.64.1.437-444.1990
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Epstein-Barr virus DNA in lymphoblastoid cell lines are correlated with frequencies of spontaneous lytic growth but not with levels of expression of EBNA-1, EBNA-2, or latent membrane protein

Abstract: The process of Epstein-Barr virus (EBV)-induced transformation of human B lymphocytes results in a cell line that is a mixture of latently and lytically infected cells, with the lytic cells composing roughly 5% to less than 0.0001% of the overall population. A set of nine normal lymphoblastoid cell lines that span a 100to 200-fold range in average EBV DNA content were studied, and the frequency with which these cells entered a lytic phase of viral growth correlated with their EBV DNA copy number (as a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 65 publications
1
7
0
1
Order By: Relevance
“…Furthermore, the average amount of EBNA-1 did not correlate with the average number of genome copies present per cell. This same observation has been made with viral RNA: the amount of RNA homologous to the EBNA-1 gene per cell is rather constant in a set of cell lines similar to those studied here (13).…”
Section: Thlb-4 Thlb-5supporting
confidence: 79%
“…Furthermore, the average amount of EBNA-1 did not correlate with the average number of genome copies present per cell. This same observation has been made with viral RNA: the amount of RNA homologous to the EBNA-1 gene per cell is rather constant in a set of cell lines similar to those studied here (13).…”
Section: Thlb-4 Thlb-5supporting
confidence: 79%
“…Viral reactivation in herpesviruses is best studied by monitoring the appearance of the viral antigens associated with productive viral infection (6,23,33,35). The infected cells used for experimentation are usually damaged from the fixation procedure necessary to detect viral antigens.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that some BLCLs do not produce EBV, whereas others are associated with virus production. [21][22][23] Katz et al 24 showed that only 40% of BLCLs grown from EBV-LPD lesions contain replicating EBV DNA. Therefore, it is possible that in vivo some transformed B cells do not produce virus, resulting in normal levels of EBV DNA in some patients with EBV-LPD.…”
Section: Discussionmentioning
confidence: 99%